Raw data and code for the paper: Do Nearctic hover flies (Diptera: Syrphidae) engage in long-distance migration? An assessment of evidence and mechanisms - Clem, Scott; Hobson, Keith; Harmon-Threatt, Alexandra (University of Illinois at Urbana-Champaign, 2022)
This dataset is for the publication "Do Nearctic hover flies (Diptera: Syrphidae) engage in long-distance migration? An assessment of evidence and mechanisms." It consists of 11 Excel spreadsheets and 4 R scripts which correspond to the analyses which were conducted.

Paper abstract:
Long-distance insect migration is poorly understood despite its tremendous ecological and economic importance. As a group, Nearctic hover flies (Diptera: Syrphidae: Syrphinae), which are crucial pollinators as adults and biological control agents as larvae, are almost entirely unrecognized as migratory despite examples of highly migratory behavior among several Palearctic species. Here, we examined evidence and mechanisms of migration for four hover fly species (Allograpta obliqua, Eupeodes americanus, Syrphus rectus, and Syrphus ribesii) common throughout eastern North America using stable hydrogen isotope (δ2H) measurements of chitinous tissue, morphological assessments, abundance estimations, and cold-tolerance assays. While further studies are needed, non-local isotopic values obtained from hover fly specimens collected in central Illinois support the existence of long-distance fall migratory behavior in Eu. americanus, and to a lesser extent S. ribesii and S. rectus. Elevated abundance of Eu. americanus during the expected autumn migratory period further supports the existence of such behavior. Moreover, high phenotypic plasticity of morphology associated with dispersal coupled with significant differences between local and non-local specimens suggest that Eu. americanus exhibits a unique suite of morphological traits that decrease costs associated with long-distance flight. Finally, compared to the ostensibly non-migratory A. obliqua, Eu. americanus was less cold tolerant, a factor that may be associated with migratory behavior. Collectively, our findings imply that fall migration occurs in Nearctic hover flies, but we consider methodological limitations of our study in addition to potential ecological and economic consequences of these novel findings.
Keywords: Insect migration; hover fly; Syrphidae; stable isotopes; deuterium; morphometrics; cold tolerance